Development of Guided Inquiry Based Teaching Materials Enriched with Augmented Reality - Venin Kharisma Noviantia; Munzil Munzil; Vita Ria Mustikasari; Erni Yulianti (Universitas Negeri Malang, 2021)
The purpose of this research and development is to produce Guided-Inquiry Based Teaching Materials Enriched by Augmented Reality (AR) on the subject of light and optics for 8th grade which is feasible and valid, as a teaching materials during the COVID-19 pandemic. This research and development using Lee and Owen’s method. However, it was narrowed down into 3 stages only, which are: assessment/analysis, design, and development stage. The teaching material’s validity was obtained from expert’s validation result, while the feasibility was obtained from the feasibility test on the students. Developed teaching materials takes form of an A5 sized pocket book, and discuss about the basic competencies in the subject of light and optics. Subject delivery served through learning module, learning video, and AR technology on image formation as well as using Google Form as student worksheet. The validation result shows that developed teaching materials are feasible and valid with score percentage more than 61 percent.